Illustrating Patriarchy through Sexual Violence Narratives: A Sara Mills CDA Framework - Aisha Ganesh Ratnasari; Merry Andriani (Hasanuddin University, 2025)
Patriarchy has affected women’s lives in every sector such as education, workplace, and family. Many forms of patriarchy in affecting women’s lives such as limitation of adequating education, raising an opinion, until experienced the violence including sexual violence. Patriarchy representation also available in media discourse, namely Jakarta Post text news. This research aimed to inquire how sexual violence as the form of patriarchy affect women’s live through Jakarta Post text news. A qualitative descriptive study and Sara Mills Critical Discourse Analysis were employed in this research. There are five topics and 11 results for the data, namely women positions as the victim, male position as the perpetrators, women objectification, male dominance, and oppression of women voices. Revealing the patriarchy representation, women are always experiencing the victim blaming and male accountability was erased.